2022
DOI: 10.1002/deo2.163
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of endoscopic submucosal resection with ligation and endoscopic submucosal dissection for small rectal neuroendocrine tumors: A multicenter retrospective study

Abstract: Objectives Endoscopic submucosal resection with band ligation (ESMR‐L) and endoscopic submucosal dissection (ESD) are both standard endoscopic resection methods for rectal neuroendocrine tumors (NETs) <10 mm in size. However, there is no definitive consensus on which is better. Here, we compared the efficacy of ESMR‐L and ESD for small rectal NETs. Methods This was a multicenter retrospective cohort study including 205 patients with rectal NETs who underwent ESMR‐L or E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In the ESMR-L procedure, the lesion is aspirated, the submucosa is elevated, and the area is strangulated with band ligation and resected using a snare, thereby achieving free vertical margins. Matsuno et al reported that both ESMR-L and ESD showed similar high complete resection rates for small rectal neuroendocrine tumors [ 12 ]. They concluded that considering the shorter procedure time and shorter hospitalization period, ESMR-L is the more efficient treatment method, especially for less-experienced endoscopists.…”
Section: Discussionmentioning
confidence: 99%
“…In the ESMR-L procedure, the lesion is aspirated, the submucosa is elevated, and the area is strangulated with band ligation and resected using a snare, thereby achieving free vertical margins. Matsuno et al reported that both ESMR-L and ESD showed similar high complete resection rates for small rectal neuroendocrine tumors [ 12 ]. They concluded that considering the shorter procedure time and shorter hospitalization period, ESMR-L is the more efficient treatment method, especially for less-experienced endoscopists.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst these are superior to standard polypectomy, they still have high rates of involvement in the deep margin resection, especially in lesions greater than 5 mm. However, a recent study comparing EMR-L vs. ESD in lesions less than 10 mm did not demonstrate a significant difference in R0 resection rates between the two techniques [19]. Therefore, for smaller lesions the choice of resection technique can be determined by the endoscopist's experience and assessment of the lesion.…”
Section: Endoscopic Therapymentioning
confidence: 98%
“…There are several different endoscopic resection options. These include standard snare polypectomy, endoscopic mucosal resection (EMR), EMR-band ligation, EMR-cap fitted, EMR-underwater, EMR-ligation (EMR-L), endoscopic submucosal dissection (ESD) and ESD muscle ligation (ML) [17,[19][20][21].…”
Section: Endoscopic Therapymentioning
confidence: 99%
“…[42,[74][75][76] Modified EMR and ESD have similar benefits. [77][78][79] For endoscopic full-thickness resection, the German registry reported favorable outcomes in 40 cases (median procedure time, 18.5 minutes; negative margins in all cases). [80] Reliable endoscopic resection should be performed using appropriate methods based on an accurate preoperative diagnosis.…”
Section: Local Excisionmentioning
confidence: 99%